Customer Relationship Management : Concept, Strategy, and Tools - Kumar, V (Springer, 2015)
Customer relationship management (CRM) as a strategy and as a technology has gone through an amazing evolutionary journey. The initial technological approach was followed by many disappointing initiatives only to see the maturing of the underlying concepts and applications in recent years. Today, CRM represents a strategy, a set of tactics, and a technology that have become indispensible in the modern economy. This book presents an extensive treatment of the strategic and tactical aspects of customer relationship management as we know it today. It stresses developing an understanding of economi.